Possible role of Spironolactone in a sample of Iraqi patients with acute central serous chorioretinopathy: Spironolactone in acute csr - Hameed, Marwa Majeed; Rasheed, Ahmed Majeed; Hameed, Furkaan Majeed (AL-Kindy College Medical Journal, 2022)
Background: Central serous chorioretinopathy (CSCR) is an idiopathic condition aggravated by exogenous or endogenous glucocorticoids. Vascular deregulation in the choroid is a new hypothesis regarding central serous chorioretinopathy occurrence. The inhibition of choroidal mineralocorticoid receptors has a great role in shortening the duration of CSCR by inhibiting choroidal vasodilatation and leak. Objective: To assess the effect of oral spironolactone on subretinal fluid, central macular thickness and visual acuity in patients with acute CSCR compared to observation. Subjects and Methods: a hospital based, randomized clinical trial carried out at outpatient clinic in Ibn-Alhaitham Teaching Eye Hospital/ Baghdad, enrolling 60 patients with acute unilateral CSCR, allocated randomly (every other patient) to either receiving spironolactone 25 mg orally, twice daily for 2 months (30 patients) or observation only (30 patients). The follow-up included visual acuity measurement, central macular thickness and subretinal fluid height examinations by ocular coherence tomography (OCT) at one- and two-months post enrollment for all patients. Results: Complete absorption of subretinal fluid was observed in 21(70%) of the eyes in the treatment group and in 6(20%) in the control group at two-months. Visual acuity and mean macular thickness improved significantly in both groups at the one- and two- months, mean changes was larger in treatment group compared to control group at the two-month-follow up endpoint. Conclusion: Oral spironolactone imparted greater improvement in central macular thickness and faster resolution of sub retinal fluid in patients with acute central serous chorioretinopathy versus observation.